(3eNJUQ JGQjN OeTb dGHf YSGcQs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3Ydj Hf GdMSf Hf gHI Gddg GdOeTbj , CHh GdbGSe, KbI GdOjf GHf YSGcQ,J (B600 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI gGQhf GdQTjO s
(3BNQgG (B:s
(3jfJgi HJQLeI jRjO Hf GdbYbGY s
(3GdehLhO efg GdLRA GdSGHY hGdYTQhfs
(3GfXQ Qbe (B451 (3h(B788s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdJGQjNs